RELEVANSI NEURO-LINGUISTIC PROGRAMMING (NLP) TERHADAP POLA KOMUNIKASI GURU DALAM PEMBELAJARAN - Qadhafi, Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Effective communication between teachers and students is a key element in creating meaningful learning experiences. One approach that can enhance the quality of teacher communication is Neuro-Linguistic Programming (NLP), which offers practical techniques to understand and influence thought patterns and behavior. This study aims to examine the relevance of NLP to teachers' communication patterns in learning through a descriptive qualitative approach using literature review methods. The focus is on three NLP techniques: rapport, reframing, and modeling. The results show that rapport helps teachers build emotional closeness and trust with students, reframing enables the transformation of negative perceptions into positive ones during learning, and modeling encourages learning through the emulation of successful strategies and behaviors. These three techniques strengthen the role of the teacher as an inspiring and empowering communicator. This study recommends that teachers participate in NLP training to gain deeper understanding and practical skills for applying this approach effectively in educational settings